2012
DOI: 10.1088/1748-9326/7/4/045602
|View full text |Cite
|
Sign up to set email alerts
|

Migration and risk: net migration in marginal ecosystems and hazardous areas

Abstract: The potential for altered ecosystems and extreme weather events in the context of climate change has raised questions concerning the role that migration plays in either increasing or reducing risks to society. Using modeled data on net migration over three decades from 1970 to 2000, we identify sensitive ecosystems and regions at high risk of climate hazards that have seen high levels of net in-migration and out-migration over the time period. This paper provides a literature review on migration related to eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 30 publications
1
49
1
2
Order By: Relevance
“…Coastal regions and mega-deltas in particular are, however, net receiving areas in terms of migration. de Sherbinin et al (2012) show that globally between1970s and 2000 censuses, there has been a marked population drift to coastal areas. Most of this net influx is to urban centres, and much of the net increase in cities in deltas is from surrounding delta regions.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal regions and mega-deltas in particular are, however, net receiving areas in terms of migration. de Sherbinin et al (2012) show that globally between1970s and 2000 censuses, there has been a marked population drift to coastal areas. Most of this net influx is to urban centres, and much of the net increase in cities in deltas is from surrounding delta regions.…”
Section: Introductionmentioning
confidence: 99%
“…58 While most migration in response to drought is temporary, over the 1970s to 1990s, an average of 5.1 million people per decade migrated permanently out of high drought risk zones: 2.3 million in Africa, 2.3 million in South-Central Asia, and the remainder in the Caribbean and South-Eastern Asia. 59 The decision to migrate during a drought is a complex one. Drought erodes food and livelihood security, particularly for households that rely on rain-fed agriculture.…”
Section: Droughtmentioning
confidence: 99%
“…Issues frequently discussed include (i) a potential legal framework for the protection of environmental migrants (Biermann and Boas 2009;Williams 2008); (ii) the potential of environmental migration to induce conflict (Reuveny 2007;Warnecke, Tänzler, and Vollmer 2010. ); (iii) the drivers of environmental migration or migration in general Hugo 2011); (iv) the difficulty to distinguish between climate-induced migration and otherwise motivated migration (such as politically or economically motivated); (v) the scope of the issue and reliable projections with regard to actual numbers and future scenarios (Döös 1997;de Sherbinin et al 2012); and (vi) migration as a means of adaptation that should actually be perceived in a more positive manner and be facilitated by international and national policy makers (McLeman and Smit 2006;Tacoli 2009). …”
Section: Climate Change and Migrationmentioning
confidence: 99%
“…For example, a net movement of people from rural to urban areas is expected to continue regardless of any environmental drivers. Moreover, especially in India and the PRC, it has been shown that people have tended to move out of marginal dry and mountainous regions and to move broadly into coastal areas (Seto et al 2011;de Sherbinin et al 2012). Thus, the number of people living in the especially vulnerable environments of coastal megacities will probably increase, just as the hazards they are facing also become exacerbated by climate change.…”
Section: The Nexus Of Climate Change and Migration In Asiamentioning
confidence: 99%
See 1 more Smart Citation